Monocyte to Lymphocyte Ratio in Peripheral Blood of Tuberculous Meningitis with HIV Patients in Tertiary Hospital in West Java - Amalia, Ridha; Turbawaty, Dewi Kartika; Sugianli, Adhi Kristianto; Aminah, Siti (International Journal of Integrated Health Sciences, 2018)
Objective: To describe peripheral blood monocyte to lymphocyte (ML) ratio in tuberculous meningitis (TBM) patients with human immunodeficiency virus (HIV) infection in Dr. Hasan Sadikin General Hospital Bandung as a tertiary hospital in West Java Province, Indonesia.Method: A cross-sectional study with retrospective data approach was done in Dr. Hasan Sadikin General Hospital, Bandung. Data were collected from TBM patients who were hospitalized in Dr. Hasan Sadikin General Hospital, Bandung in the period of 2014–2016. The sample size was determined using total sampling method. General data, clinical manifestation data, and laboratory finding data were collected. The ML ratio was collected and presented into three groups of percentile (25th, 25–75th and 75th) based on the pre-defined cut-off.Result: Six subjects (40%) had an ML ratio of ≤0.47 and 3 subjects had an ML ratio of ≥1.22 in TBM with HIV population. Among TBM with HIV-negative population, there were 16 subjects had ML ratio ≤0.47, and 19 subjects had ML ratio ≥1.22.Conclusion: The ML ratio in TBM with HIV infection has become additional tool for detecting the development of TBM with HIV-infected, as well as TBM with non-HIV-infected. Therefore, it could help directing the patients with clinical suspicious of TBM into the diagnosis algorithm and treatment of TBM, to have better outcome.Keywords: Human immunodeficiency virus infection,lymphocyte, monocyte, monocyte to lymphocyte ratio, tuberculous meningitis DOI: 10.15850/ijihs.v6n1.1140